Seroprevalence of Japanese encephalitis virus & West Nile virus in Alappuzha district, Kerala - Anukumar Balakrishnan (Indian Journal of Medical Research, 2017)
Background & objectives: Several outbreaks of acute encephalitis syndrome (AES) have been reported in Alappuzha district, Kerala State, India, in the past. The aetiology of these outbreaks was either inconclusive or concluded as probable Japanese encephalitis virus (JEV) infection based on clinical presentation. The role of West Nile virus (WNV) in AES outbreaks was also determined. However, the extent of WNV infection has not been studied in this region previously. A population-based cross-sectional serosurvey study was undertaken to determine the seroprevalence of JEV and WNV in Alappuzha district. Methods: A total of 30 clusters were identified from 12 blocks and five municipalities as per the probability proportional to size sampling method. A total of 1125 samples were collected from all age groups. A microneutralization assay was performed to estimate the prevalence of JEV and WNV neutralizing antibodies in the sample population. Results: Of 1125 serum samples tested, 235 [21.5%, 95% confidence interval (CI): 15.2-27.8%] and 179 (15.9%, 95% CI: 9.6-22.3%) were positive for neutralizing antibodies against WNV and JEV, respectively. In addition, 411 (34.5%, 95% CI: 26.7-42.2%) were positive for cross-reactive antibodies against flaviviruses. Interpretation & conclusions: The study showed the seroprevalence of WNV and JEV antibodies in the surveyed area and the WNV seroprevalence was greater than JEV. It is necessary to create awareness in public and adopt suitable policy to control these diseases.